Modus Kejahatan Card Trapping di Mesin ATM dalam Transaksi Perbankan - Gunawan, Ade; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Card trapping is a form of banking crime that is still common in Indonesia. This crime is committed by trapping an ATM card so that it remains stuck inside the machine. The card is then removed by the perpetrator and used to access customer funds. This study aims to explain how card trapping is carried out and why this practice is still prevalent. Using literature and media analysis, it was found that this method uses simple tools but exploits customer negligence. This article also discusses the causal factors, real-life case studies, and the impact of card trapping on customers and banking institutions. The perpetrators can drain customer accounts. The results show that despite regulations and developing security technology, card trapping crimes remain rampant due to a lack of education and preparedness in banking infrastructure.